Prevalência da infectologia ao longo da graduação - Garcia, Isabella Rossi (Universidade Federal de São Carlos, 2024)
Reflective narrative about contact with the infectious disease specialty during the Medical School at the Federal University of São Carlos and its intersection with different medical specialties as well as its importance in different areas of professional and personal life. Retrospective of experiences over six years of training and how infectious disease was present in each of them, including our basic training, our support during a pandemic and our basis for other medical specialties.
Prevalence of infectious diseases throughout graduation
Keywords: Educação médica; Aprendizagem baseada em problemas; Infectologia; Medical education; Problem-based learning; Infectious disease; CIENCIAS DA SAUDE::MEDICINA::CLINICA MEDICA